Implementasi Komunikasi Pemasaran Terpadu Dalam Upaya Meningkatkan Penjualan Produk Tumbler di Starbucks KM 57 - Asmoro, Cresentya Intan; Tayo, Yanti; Rifai, Maulana (Peneliti.net, 2024)
This study aims to determine and explain the implementation of Integrated Marketing Communication in increasing tumbler sales at Starbucks Rest Area KM 57, which is located in the Rest Area of the Jakarta-Cikampek Toll Road. In this case, the researcher seeks to obtain in-depth and detailed information about the implementation of integrated marketing communication of Starbucks Coffee Rest Area KM 57 Toll Jakarta - Cikampek. This research was conducted through Qualitative methods with data collection through observation, interviews, and documentation regarding the Implementation of Integrated Marketing Communication at Starbucks Rest Area KM 57 in increasing tumbler sales with the theory according to Firmansyah (2020) in the Implementation of integrated marketing communications, namely Direct Marketing, Sales Promotion, Public Relations, Personal Selling, Advertising, Word of Mouth Marketing, Events and Experiences, Interactive Marketing. From this implementation, Starbucks Rest Area KM 57 uses a partnership called 8 ijo in selling tumblers, besides that marketing efforts through are still carried out and assisted by baristas through personal social media.